São Caetano do Sul, Brazil and Luanda, Angola: Two realities in urban solid waste handling and management - Nakaoka , Flavio; Toledo , Renata Ferraz de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The climate emergency is the main environmental issue today. Among other aspects, coping with its effects, implies changes in the way society produces, consumes and disposes of its goods. This research aimed at characterizing and analyzing dry or recyclable Urban Solid Waste (USW) handling and management in the municipalities of São Caetano do Sul, SP, Brazil, and Luanda, in the province of Luanda, Angola, in order to contribute to recognizing challenges and potentialities to qualify this process. This is a case study with a quali-quantitative approach, carried out through a bibliographic review, survey and analysis of secondary data, documentary analysis and field visits with non-participant observations. Data analysis was carried out by triangulating methods. It was found that, even with their geographic, socio-demographic and political-economic specificities, São Caetano do Sul and Luanda have similar recycling indicators. The absence of public policies capable of promoting responsible consumption is also accompanied by lack of planning of urban spaces to promote proper USW disposal by consumers. In both cases investigated, the demand for USW recovery strategies and mechanisms that promote selective post- consumption disposal were evident, in order to benefit reintegration of waste into the production chain. It is hoped that this research can contribute to reflections on the topic, regarding the role of each actor and public policies related to proper urban solid waste handling and management.
Keywords: Selective disposal; Waste management; Recycling